Pengaruh Pendapatan Asli Daerah (PAD), Kekayaan Daerah, Sisa Lebih Pembiayaan Anggaran (SILPA) terhadap Belanja Modal dengan Petumbuhan Ekonomi sebagai Variabel Moderasi pada Pemerintah Provinsi Se- Indonesia periode 2015-2019 - Danil Sanjaya; Herlina Helmy (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to determine the effect of Regional Original Income (PAD), regional Asset and Excess Budget Financing (SILPA) on Capital Expediture with Economic Growth as a Moderating Variable in Provincial Governments throughout Indonesia 2015-2019. The data use in this study is the report on the realization of APBD for the 2015-2019 fiscal year which is available on the DJPK website. The population and sample in this study ara all provincial governments in Indonesia consisted of 34 provinces from 2015-2019 with a total of 170 data. Hypothesis testing in this study uses the Moderated Regression Analysis (MRA) test. The result show that PAD has no significant effect on capital expenditure, Regional Wealth and SILPA have a significant effect and simultaneously independent variables have a significant effect on the dependent variable, Economic Growth strengthens the influence of PAD and SILPA on capital expenditure and Economic Growth weakens Regional wealth on Capital Expenditure.